Galvanic vestibular stimulation to rehabilitate postural instability in Parkinson's disease - Pires, Anna Paula Batista de Ávila; Labanca, Ludimila; Christo, Paulo Pereira; Tavares, Maurício Campelo; Barroso, Jordana Carvalhais; Diniz, Maria Luiza; Gonçalves, Denise Utsch (Arquivos de Neuro-Psiquiatria, 2025)
Background Galvanic vestibular stimulation (GVS) is a non-invasive technique employed to rehabilitate balance by delivering low-intensity, short-duration electrical stimulation to the mastoid bones, effectively activating the vestibulospinal tract.Objective To evaluate the effects of GVS on balance in patients with Parkinson's disease (PD) and postural instability.Methods In this clinical study, 25 PD patients with postural instability in the ON phase (best effect of dopaminergic medication) underwent GVS. Balance was assessed using the Berg Balance Scale (BBS), the Timed Up and Go (TUG) test, and posturography on a force platform. Electrical current intensity was progressively increased between the mastoids, starting at 1.0 mA and reaching 3.5 mA by the 6th session, with this level maintained until the 8th session. Stimulation duration began at 9 minutes in the 1st session, increased to 30 minutes by the 3rd session, and was sustained through the 8th session.Results A blinded comparison of pre- and post-GVS evaluations demonstrated significant improvements in BBS (p = 0.00001) and TUG (p = 0.00003) scores. Posturography showed an increase in the stability limit area (p = 0.026) and the general balance index (p = 0.001).Conclusion In the therapeutic management of postural instability in PD, GVS emerges as a promising complementary strategy for enhancing balance. Further research is needed to determine whether these improvements persist after GVS cessation.Registration of Clinical Trial: https://ensaiosclinicos.gov.br/rg/RBR-22j8728.
Keywords: Parkinson Disease; Neurodegenerative Diseases; Postural Balance; Electric Stimulation; Rehabilitation